A conclusione delle ChLA, seconda serie - Nicolaj, Giovanna (Scrineum, 2020)
As the second serie of the Chartae Latinae Antiquiores is approaching its conclusion with the publication of the last volume, this paper contains some final considerations on the whole editorial project and the decision to extend it to the 9th century, the role of documentary sources in the Carolingian Age, the countries involved in the project and the number of documents included or excluded from the serie.